1992
DOI: 10.1152/ajpheart.1992.263.1.h271
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of 17 beta-estradiol on rabbit coronary artery contractile responses to endothelin-1

Abstract: We assessed the acute effect of 17 beta-estradiol on coronary artery constrictor responses to endothelin-1. 17 beta-Estradiol significantly shifted endothelin-1, calcium, or BAY K 8644 concentration-dependent contraction curves to the right in endothelium-denuded coronary arteries isolated from nonpregnant female rabbits. The -log 50% effective dose (ED50) of calcium in high KCl medium (100 mM) was 3.8 +/- 0.11 in control and 3.2 +/- 0.1 and 2.8 +/- 0.12 after incubation with 17 beta-estradiol (1 and 10 microM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
2
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 0 publications
5
94
2
2
Order By: Relevance
“…Second, oestrogen could act as an antioxidant [27] and thereby attenuate the degradation of NO by oxygen free radicals. Oestrogens could also modulate the vasoactive action of other endothelium-derived factors, such as prostacyclin and endothelin [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Second, oestrogen could act as an antioxidant [27] and thereby attenuate the degradation of NO by oxygen free radicals. Oestrogens could also modulate the vasoactive action of other endothelium-derived factors, such as prostacyclin and endothelin [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have documented that E2 can induce relaxation of coronary arteries, reverse acetylcholine-induced vasoconstriction and improve exercise-induced myocardial ischemia in women with coronary artery disease (29)(30)(31)(32). Collins et al (33) showed that E2 decreases acetylcholine-induced coronary artery responses only in women, but not in men.…”
Section: Estrogen and Vascular Tonementioning
confidence: 99%
“…However, systemic effects of estrogens do not account fo ~" the majority of the observed atheroprotective effects of E2 [2.3,15,16]. In an effort to reveal additional pathways that may mediate the atheroprotective effects of E2, direct effects of E2 ol ~, vascular cells are currently being investigated (reviewed in [1 '] Direct effects of E2 on vascular cell function were first suggested decades ago [7,18] and have since been shown both in whole animal and in vitro studies [10,[19][20][21][22][23][24][25][26][27][28][29][30]. However, the signaling pathways involved in the direct effects of E2 on vascular cells are not yet characterized.…”
Section: Introductionmentioning
confidence: 99%